Developing case studies in teacher education: Spotlighting socioscientific issues - DeCoito, Isha; Fazio, Xavier (Innovations in Science Teacher Education, 2016)
Despite the growing corpus of research on socioscientific issues (SSI) in science education, the relevant implications for science teacher education remain relatively unexplored. There is a need for preservice and inservice programs that challenge teachers’ discomfort and suggest means for teaching controversial issues. In order to better inform these efforts, it is necessary to learn more about how preservice teachers use science curriculum materials dealing with SSI in science learning environments. One avenue for exploring SSI with teacher candidates (TCs) is through case studies. Case studies have had extensive usage in numerous disciplines; in science education case studies can take into consideration many different facets of science including epistemology, scientific content, and the nature of science. With the goal of gaining a better understanding of how to support TCs in fostering their future students’ understanding of SSI, this research study was conducted while TCs were supported by their instructor in the development of case studies about SSI in a secondary science methods course. This paper outlines the processes involved in preparing and supporting TCs while they assumed dual roles – curriculum developers and co-constructors of knowledge – as they developed their case studies. Additionally, it provides a structure for developing case studies and highlights an example of a case study focusing on genetically modified salmon. Further, this assignment provides a useful framework for science teacher educators wishing to create appropriate SSI assignments for TCs in science education.